(Dis)Connected: Finding the link between problematic use of internet, parent-child communication and academic performance in emerging adults - Alda Portugal; Carina Almada; Luciana Sotero; Ana Paula Relvas (Cyberpsychology: Journal of Psychosocial Research on Cyberpspace, 2025)
Information and Communication Technologies (ICT) play a central role in the lives of emerging adults, offering both opportunities and challenges. While ICT facilitates communication and access to information, its problematic use has raised concerns about its impact on family relationships and academic performance during this developmental stage. This cross-sectional study aims to describe the use of ICT in academic context and analyse differences between groups considering the problematic use of the internet, the perception of academic performance and parent-child communication in a sample of college students (N = 201, aged between 18 to 29). In addition to instruments for sociodemographic characterisation and of ICT use, Generalized Problematic Internet Use Scale-2 and Perception Scale of Parenting Communication-Emerging Adults were used. The results suggest that young people with problematic use of internet for non-academic purposes tend to report poorer communication with their parents, particularly their fathers. Additionally, half of the sample exhibited moderate problematic use of the internet. These results are relevant for professionals working with young adults, such as college professors, as well as for young adults themselves and their parents. Professors may benefit from implementing structured guidelines for ICT use in the classroom to promote academic engagement while minimizing distractions. For young adults, the findings emphasize the importance of developing self-regulation strategies to balance digital life, enhance academic performance, and maintain healthy relationships. Parents are encouraged to foster open communication and support positive family dynamics to mitigate the negative effects of problematic internet use.